1985
DOI: 10.1021/ed062p173
|View full text |Cite
|
Sign up to set email alerts
|

Monomer reactivity ratios: Acrylic acid-methylmethacrylate copolymerization in dimethylsulfoxide

Abstract: Determination of reactivity ratios for the system acrylic acid / methyl methacrylate in dimethylsulfoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
4
7
0
Order By: Relevance
“…While there are differences between the two methods, it is clear that AA is approximately three times more reactive than APMD, and hence it is expected that copolymers will contain a greater proportion of AA, and lower levels of the repellent carrying APMD, than anticipated simply from the feed composition. This finding is in agreement with previous literature showing that, as a monomer becomes bulkier, its reactivity tends to decrease; for example, when acrylic acid was copolymerised with methyl methacrylate, the reactivity ratio of the acrylic acid was 1.50, and for the bulkier methyl methacrylate it was 0.48 [ 14 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While there are differences between the two methods, it is clear that AA is approximately three times more reactive than APMD, and hence it is expected that copolymers will contain a greater proportion of AA, and lower levels of the repellent carrying APMD, than anticipated simply from the feed composition. This finding is in agreement with previous literature showing that, as a monomer becomes bulkier, its reactivity tends to decrease; for example, when acrylic acid was copolymerised with methyl methacrylate, the reactivity ratio of the acrylic acid was 1.50, and for the bulkier methyl methacrylate it was 0.48 [ 14 ].…”
Section: Resultssupporting
confidence: 92%
“…Given the large disparity in monomer inclusion in the copolymer, reactivity ratios ( r = the ratio of the monomers in copolymerisation [ 14 ]) were calculated by application of conventional linearization methods, namely the Finemann–Ross (FR) and Kelen–Tüdós (KT) methods [ 15 ]. The results are summarised in Figure 2 , with more details of the approach and plots available in the Supplementary Materials ( Tables S1 and S2 , Figures S4 and S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…30 We found that an increase in AA proportion generally increased the surface content of -COOH groups but the content of -COOH groups was lower than the expected AA fraction. Similar observations were found in other studies and might be attributed to different degrees of copolymerisation in relation to monomer reactivity ratios, 31 polymer chain mobilities of PAA and poly(alkyl methacrylates) in the subsurface layer which is beyond the sampling depth (<10 nm) of XPS, as well as reorientation of the hydrophilic functional group to avoid air exposure. 32 Our results demonstrated that the surface hydrophobicity of coated surfaces correlates well with the chemical compositions, in accordance with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were found in other studies and might be attributed to different degrees of copolymerisation in relation to monomer reactivity ratios, 31 polymer chain mobilities of PAA and poly(alkyl methacrylates) in the subsurface layer which is beyond the sampling depth (<10 nm) of XPS, as well as reorientation of the hydrophilic functional group to avoid air exposure. 32 Our results demonstrated that the surface hydrophobicity of coated surfaces correlates well with the chemical compositions, in accordance with the literature. 33,34 At relatively the same -COOH ratios, surfaces presenting -(CH 2 ) 3 CH 3 groups exhibited a higher hydrophobicity than -CH 3 and -CH 2 CH 3 groups whereas the latter two did not differ signicantly.…”
Section: Discussionsupporting
confidence: 89%
“…Copolymers of itaconic acid and methylmethacrylate have been synthesized by emulsion [13] and solution polymerization [14,15]. Methyl methacrylate and acrylic acid has been synthesized by charge-transfer copolymerization, solution and bulk polymerization [16][17][18][19]. Free radical copolymerization of styrene with maleic anhydrides has been studied by various workers [20,21] using azobisisobutronitrile and benzoyl peroxide as initiators in bulk as well as in various solvents.…”
Section: Methodsmentioning
confidence: 99%